The role of host defences in Covid 19 and treatments thereof - Maurizio Dattilo (BMC, 2020)
Abstract Hydrogen sulfide (H2S) is a natural defence against the infections from enveloped RNA viruses and is likely involved also in Covid 19. It was already shown to inhibit growth and pathogenic mechanisms of a variety of enveloped RNA viruses and it was now found that circulating H2S is higher in Covid 19 survivors compared to fatal cases. H2S release is triggered by carbon monoxide (CO) from the catabolism of heme by inducible heme oxygenase (HO-1) and heme proteins possess catalytic activity necessary for the H2S signalling by protein persulfidation. Subjects with a long promoter for the HMOX1 gene, coding for HO-1, are predicted for lower efficiency of this mechanism. SARS-cov-2 exerts ability to attack the heme of hemoglobin and other heme-proteins thus hampering both release and signalling of H2S. Lack of H2S-induced persulfidation of the KATP channels of leucocytes causes adhesion and release of the inflammatory cytokines, lung infiltration and systemic endothelial damage with hyper-coagulability. These events largely explain the sex and age distribution, clinical manifestations and co-morbidities of Covid-19. The understanding of this mechanism may be of guidance in re-evaluating the ongoing therapeutic strategies, with special attention to the interaction with mechanical ventilation, paracetamol and chloroquine use, and in the individuation of genetic traits causing increased susceptibility to the disruption of these physiologic processes and to a critical Covid 19. Finally, an array of therapeutic interventions with the potential to clinically modulate the HO-1/CO/H2S axis is already available or under development. These include CO donors and H2S donors and a boost to the endogenous production of H2S is also possible.